2018
DOI: 10.2147/ijgm.s164903
|View full text |Cite
|
Sign up to set email alerts
|

Understanding short-term blood-pressure-variability phenotypes: from concept to clinical practice

Abstract: Clinic blood pressure (BP) is recognized as the gold standard for the screening, diagnosis, and management of hypertension. However, optimal diagnosis and successful management of hypertension cannot be achieved exclusively by a handful of conventionally acquired BP readings. It is critical to estimate the magnitude of BP variability by estimating and quantifying each individual patient’s specific BP variations. Short-term BP variability or exaggerated circadian BP variations that occur within a day are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 138 publications
0
52
0
5
Order By: Relevance
“…Moreover, at multivariate analysis, after adjustment for sex and body mass index, the strongest predictors of 24-h systolic and diastolic wSD were the 24-h urinary metanephrines, underlying the feasible role of catecholamines overproduction in the BPV changes. The wSD represents the average of daytime and night-time BP that has been adjusted for the duration of the day and night period to account for day-night BP changes [8] and it allows to exclude the interference of night-time BP fall on overall BPV, and consents a more precise assessment of the clinical value of 24-h BPV [39]. Therefore, together with ARV, the wSD is an index unaffected by day-to-night BP changes and it should be preferred for the BPV evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at multivariate analysis, after adjustment for sex and body mass index, the strongest predictors of 24-h systolic and diastolic wSD were the 24-h urinary metanephrines, underlying the feasible role of catecholamines overproduction in the BPV changes. The wSD represents the average of daytime and night-time BP that has been adjusted for the duration of the day and night period to account for day-night BP changes [8] and it allows to exclude the interference of night-time BP fall on overall BPV, and consents a more precise assessment of the clinical value of 24-h BPV [39]. Therefore, together with ARV, the wSD is an index unaffected by day-to-night BP changes and it should be preferred for the BPV evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Although office blood pressure (BP) values remain the gold standard for the diagnosis of hypertension, the measurement of BP variability (BPV) in addition to office BP, has been demonstrated to have physiopathological and prognostic importance [7,8]. Short-term BPV refers to the BP changes that occur within a day [24 hours (24-h)], and it is influenced by several mechanisms, such as central neural factors, reflex autonomic modulation, changes in the elastic properties of arteries, humoral systems (i.e., insulin, angiotensin II, endothelin-1, bradykinin, and nitric oxide), rheological and mechanical factors [8]. Several studies have shown that higher 24-h BPV, assessed by 24-h ambulatory blood pressure monitoring (24-h ABPM), independently of mean office BP values, is clinically important, as this might increase cardiovascular events, mortality, and hypertension-mediated organ damage [9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure variability (BPV) is characterized by marked spontaneous oscillations over short-term or long-term time periods depending on the interplay of different cardiovascular control systems, such as the baroreceptor reflex, the vascular myogenic response, as well as changes in behavioural and emotional mechanisms [ 85 ]. The ability to monitor short-term instantaneous BP changes in time is based on the non-invasive “volume-clamp” method by Peňáz in the early 1970s [ 86 , 87 ].…”
Section: Autonomic Nervous System Dysregulation As a Potential Mecmentioning
confidence: 99%
“…There are several mechanisms having an impact on BPV; e.g., very short-and short-term BPV is caused by humoral, rheological, behavioural, and emotional factors; impact of reflex and central autonomic modulation or arterial elasticity; mid-and long-term BPV, by behavioural factors, arterial stiffness, as well as seasonal climatic change, or poor control of blood pressure in treated patients [26]. Detailed description of the BPV pathomechanism is beyond the scope of this review and may be found elsewhere [32][33].…”
Section: Patomechanismmentioning
confidence: 99%